Biomass-Derived Porous Carbon Materials: Synthesis and Catalytic Applications - De, Sudipta; Balu, Alina Mariana; van der Waal, Jan C.; Luque, Rafael (ChemCatChem, 2015)
Novel biomass‐derived porous carbons are attractive candidates for the preparation of carbon‐supported catalysts with a wide range of catalytic applications. Such carbonaceous catalysts are environmentally benign and could provide a cost‐competitive advantage as compared to existing heterogeneous catalysts. Tunable surface properties of carbon materials and excellent physical properties (e.g., hydrophobicity, chemically inert nature, etc.) are compatible with diverse catalysis reactions including organic transformations, as well as electro‐ and photochemical processes in aqueous solutions. This contribution provides an overview on the utilization of different biomass feedstocks and/or biomass‐derived precursors for the synthesis of carbonaceous materials to design advanced catalytic systems and their emerging applications in catalysis. Renewable feedstocks for sustainable chemistry: Developing advanced materials from renewable precursors is the way forward to a sustainable future. This contribution discusses the synthesis and functionalization of porous carbonaceous materials and their wide range of catalytic applications in organic synthesis, biomass transformation, fuel cells, electrocatalysis, and photocatalysis.